Eastern hot dry rock target prospect: a case history - Schubert, C. E.; Maxwell, J. C.; Johnson, W. J. (D'Appolonia Consulting Engineers, Inc., Pittsburgh, PA (USA), 1980)
The Eastern Hot Dry Rock Target Prospect is located in a corridor between Smith Island, Maryland on Chesapeake Bay and the southern tip of Assateague Island, Virginia on the Atlantic Ocean. The prospect was selected for investigation based on anomalously high heat flow values and thermal gradients previously determined. The exploration program was aimed at locating the most favorable location within the site area for the targeting of a deep test borehole for HDR heat extraction. The program consisted of an aeromagnetic survey, gravity/magnetic analysis, time-domain electromagnetic (TDEM) survey, Vibroseis seismic reflection profiling, drilling and logging of four 300-meter borings, and the reopening and logging of an abandoned oil exploration hole. The preliminary results of this nearly completed study indicate that the area has potential for the extraction of heat using the Hot Dry Rock concept.